Assessment of factors affecting vaccine cold chain management practice in public health institutions in east Gojam zone of Amhara region - Hewan Adam Bogale; Abebe Feyissa Amhare; Alemtsehay Adam Bogale (BMC, 2019)
Abstract Background Maintaining quality of vaccines is one of the main challenges of immunization programs in Ethiopia. The objective of this study is to assess the factor affecting vaccine cold chain management practice in immunization health institutions in East Gojam zone of Amhara region, Ethiopia. Method An institutional based cross-sectional study was conducted from March to April 2017 in ten districts of East Gojam zone of Amhara Region. Descriptive statistics and Logistic regression analysis were carried out to identify factors related to the practice of cold chain management. Result Among 60 health institutions, only 46(76.7%) had functional refrigerators. Twenty-one (35%) had a functional generator for backup service and 28(46.6%) had a car/motorbike for transportation of vaccines in case of refrigerator/power failure. Twenty-nine (48.3%) had known the correct vaccine storage temperature (2 °C - 8 °C) in the refrigerator and the results of this study revealed that only 23(38.3%) of respondents had sufficient knowledge about vaccine cold chain management. The finding of this study also revealed that 35(58.3%) had appropriate vaccine cold chain management practice and the rest 25(41.7%) had inappropriate practice. Logistic regression showed us the knowledge gap and profession were significantly associated with vaccine cold chain management practice at P < 0.05. Conclusion This study indicates that there was a knowledge gap of health workers who are working on cold chain management. There is an urgent need to improve knowledge and practice on cold chain management through improved supervision and training at a different level of health care system.